AIRPORT SAFETY RISK EVALUATION BASED ON FUZZY ANP AND FUZZY AHP - Ozdemir, Yavuz; Basligil, Huseyin; Ak, Muhammet Fatih (WORLD SCIENTIFIC PUBL CO PTE LTD, 2016)
Assessment and management of risks in the aviation sector is a difficult problem. Risk management is the part of the overall management activities of the aviation sector which includes whole activities that provides completely secure manner with standards and applications. There are many variables and uncertainties that affect aviation risk process. In this study we have implemented multi criteria-decision making techniques, fuzzy Analytic Network Process (ANP) and fuzzy Analytic Hierarchy Process (AHP) for evaluation of airport safety risk criteria and the results of both algorithms are compared.
Keywords: Computer Science